Parental knowledge, vaccine hesitancy, and practices regarding seasonal influenza vaccination for preschool-aged children in Shenzhen, China: Insights from a cross-sectional survey - Wu Li; Hui-ling Tan; Chun-yan Zhuang; Jun-yu Li; Xu Xie; Gang Li (PLoS ONE, 2026)
Background Seasonal influenza poses a substantial health threat to children under 5 years of age. Despite recommendations for annual seasonal influenza vaccination (SIV), coverage among preschool-aged children in China remains low. Vaccine hesitancy is an important barrier to vaccine uptake. This study assessed parental knowledge, vaccine hesitancy, and practices regarding SIV for preschool-aged children in Shenzhen, China, and identified factors associated with hesitancy. Methods A cross-sectional online survey was conducted from September to December 2025 using a multistage sampling strategy across six administrative districts of Shenzhen. Parents of children aged 0–5 years were recruited from community health service centers and kindergartens/childcare institutions. An adapted Chinese version of the Parental Attitudes toward Childhood Vaccines (PACV) scale was used to assess hesitancy toward SIV. Parents’ knowledge regarding influenza and SIV, as well as SIV practices, were assessed and scored. Independent factors associated with hesitancy scores were identified using multivariable linear regression, and factors associated with binary hesitancy outcomes were conducted using multivariable logistic regression. Sensitivity analyses excluding the behavioral PACV items were also performed. Results A total of 17,955 parents were included in the final analysis, and 19.16% reported that their child had received SIV in the past year. The mean PACV hesitancy score was 32.26 ± 18.50, and 19.42% of parents (3,487/17,955) were classified as vaccine hesitant. The highest proportions of hesitant responses were related to concerns about serious adverse reactions (69.47%), the safety of repeated annual vaccination (55.61%), and doubts regarding vaccine effectiveness (52.68%). Higher knowledge and vaccination practice scores were independently associated with lower levels of vaccine hesitancy in both multivariable linear and logistic regression analyses (both P < 0.001). Additionally, older parental age, Shenzhen household registration, employment in enterprises/public institutions, middle-level household income, kindergarten attendance, obtaining vaccine information from kindergartens and relatives/friends were negatively associated with vaccine hesitancy in multivariable logistic regression analyses (all P < 0.05). Sensitivity analyses yielded generally consistent findings. Conclusion Parental hesitancy toward SIV among preschool-aged children in Shenzhen was low-to-moderate and was associated with knowledge, prior vaccination behaviors, and sociodemographic characteristics. Concerns about vaccine safety and effectiveness were the most frequently cited reasons for hesitancy. Targeted communication strategies delivered through multiple channels, together with consideration of free SIV for preschool-aged children may help improve vaccine uptake in this high-burden population.